Electro-dewatering of steel industrial sludge: Performance and metal speciation. (April 2022) - Zeng, Rui; Li, Yiming; Sha, Li; Liu, Xingxin; Zhang, Shuting
Abstract: Electro-dewatering (EDW) of sludge has been regarded as an economical and efficient dewatering method in recent years. There have been some studies on municipal sludge and industrial sludge. However, the effects of industrial sludge with high metal and salty content on the EDW performance are still unclear. Here we investigate EDW in the characteristics of steel industrial sludge, which contains large amounts of salts and metals. First, the differences between the steel industrial sludge and the other sludge in EDW treatment were explored. Then, the mechanism of interaction between the transformation of metal speciation and dewatering performance was investigated. The results indicated that the optimal 40.09% moisture content (MC) could be obtained under the operating conditions of 60 V voltage and 2.6 bar pressure. Moreover, the pH variation and electro-redox behavior can lead to the transformation of metal speciation and release charged intermediates relating to metal, causing the rise of current in the EDW process. These phenomena were beneficial to continuous dewatering. By contrast, the speciation of Ca and Zn is mainly affected by electromigration and electroosmotic flow, but the speciation of Fe and Al is more affected by the oxidizing atmosphere. This work extended the application range of EDW and filled the gap of EDW for the industrial sludge field.